Time pressure increases children’s aversion to advantageous inequity - Corbit, John (Frontiers in Psychology, 2024)
The relative contribution of intuitive and reflective cognitive systems in cooperative decision making is a topic of hot debate. Research with adults suggests that intuition often favors cooperation, but these effects are contextually sensitive. Emerging evidence has shown that in many contexts children show a tendency toward intuitive cooperation, but research investigating these processes in children is sparse and has produced mixed findings. In the current study we investigated the influence of intuitive and reflective decision processes on children’s fairness behavior by manipulating decision time. We tested (N = 158) pairs of children between 4 and 10 years of age from a rural community in Canada. Children’s decisions to accept or reject allocations of candies were either made under time pressure or after a 10-s delay. We assessed the impact of decision time on children’s aversion to inequitable distributions of resources by comparing their responses to equal allocations with either disadvantageous allocations or advantageous allocations. We found that children showed a greater age-related increase in advantageous inequity aversion when decisions were made under time pressure compared to when they were made after a delay. In contrast, we did not observe a significant impact of decision time on the development of disadvantageous inequity aversion. These findings suggest that intuitive decision processes may contribute to the development of fairness concerns in middle childhood.